Fostering communication and collaboration skills in biology education through Problem-Oriented Project-Based Learning (POPBL) - Francisco, Rendi; Ibrohim, Ibrohim; Susilo, Herawati (Universitas Islam Negeri Sumatera Utara, 2024)
The 21st-century education requires students to be able to master 21st-century skills, namely communication and collaboration skills. Communication and collaboration skills are very important for students to develop their personalities in learning, because they cause individual and group interaction to gain knowledge and learning experience from each other. 21st-century skills can be practiced through the study of biology, because biology has values of scientific nature, cooperation, respect for the opinions of others, and openness to various phenomena that have just occurred. This study aims to measure the influence of problem-based and project-based learning on the communication and collaboration skills of grade X students of SMA Negeri 10 Malang. The implementation of this study used the Problem-Oriented Project-Based Learning (POPBL) model to direct students to create creative products. The method used in this study is a quasi-experimental research using the pretest post-test nonequivalent control group design. Communication and collaboration skills were measured using instruments in the form of self-assessment and peer assessment questionnaires. The results of the questionnaire were analyzed using the analysis of covariance (ANCOVA) test. The results of the study showed that the implementation of Problem-Oriented Project-Based Learning (POPBL) has a significant effect on students' communication and collaboration skills. These findings suggest that problem-based and project-based learning models can develop students' communication and collaboration skills.